HIF-VEGF pathways are critical for chronic otitis media in Junbo and Jeff mouse mutants. - Michael T Cheeseman (Public Library of Science (PLoS), 2011)
Otitis media with effusion (OME) is the commonest cause of hearing loss in children, yet the underlying genetic pathways and mechanisms involved are incompletely understood. Ventilation of the middle ear with tympanostomy tubes is the commonest surgical procedure in children and the best treatment for chronic OME, but the mechanism by which they work remains uncertain. As hypoxia is a common feature of inflamed microenvironments, moderation of hypoxia may be a significant contributory mechanism. We have investigated the occurrence of hypoxia and hypoxia-inducible factor (HIF) mediated responses in Junbo and Jeff mouse mutant models, which develop spontaneous chronic otitis media. We found that Jeff and Junbo mice labeled in vivo with pimonidazole showed cellular hypoxia in inflammatory cells in the bulla lumen, and in Junbo the middle ear mucosa was also hypoxic. The bulla fluid inflammatory cell numbers were greater and the upregulation of inflammatory gene networks were more pronounced in Junbo than Jeff. Hif-1α gene expression was elevated in bulla fluid inflammatory cells, and there was upregulation of its target genes including Vegfa in Junbo and Jeff. We therefore investigated the effects in Junbo of small-molecule inhibitors of VEGFR signaling (PTK787, SU-11248, and BAY 43-9006) and destabilizing HIF by inhibiting its chaperone HSP90 with 17-DMAG. We found that both classes of inhibitor significantly reduced hearing loss and the occurrence of bulla fluid and that VEGFR inhibitors moderated angiogenesis and lymphangiogenesis in the inflamed middle ear mucosa. The effectiveness of HSP90 and VEGFR signaling inhibitors in suppressing OM in the Junbo model implicates HIF-mediated VEGF as playing a pivotal role in OM pathogenesis. Our analysis of the Junbo and Jeff mutants highlights the role of hypoxia and HIF-mediated pathways, and we conclude that targeting molecules in HIF-VEGF signaling pathways has therapeutic potential in the treatment of chronic OM.